The what's happening to my body? book for boys : a growing up guide for parents and sons - Madaras, Lynda (Newmarket Press, 1987)
Discusses the changes that take place in a boy's body during puberty, including information on the body's changing size and shape, the growth spurt, reproductive organs, pubic hair, beards, pimples, voice changes, wet dreams, and puberty in girls.